Analisis Kreativitas Siswa Sekolah Dasar dalam Pembelajaran Seni Melalui Kegiatan Kolase pada Masa Pandemi - Aprien Rahma Putri; Benny Aulya Rahman; Mesi Yulia Sri Insani; Farida Mayar (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2021)
This study was conducted to determine the creativity of elementary school students in learning art through collage activities during the covid-19 pandemic. The method used in this study is a literature study method, in which data collection techniques are collected through processing and analysis from various sources or references from several scientific journals that are continuous and related to the problem being studied by the researcher. Analysis of the data used in this study is to relate the problem to the theory contained in scientific journals or appropriate books based on the research being studied. The results of this study prove that learning art through collage can increase the creativity of elementary school students.